Sub-cellular proteomics of Medicago truncatula - Lee, Jeonghoon; Lei, Zhentian; Watson, Bonnie; Sumner, Lloyd W. (Frontiers in Plant Science, 2013)
Medicago truncatula is a leading model species and substantial molecular, genetic, genomics, proteomics and metabolomics resources have been developed for this species to facilitate the study of legume biology. Currently, over 60 proteomics studies of M. truncatula have been published. Many of these have focused upon the unique symbiosis formed between legumes and nitrogen fixing rhizobia bacteria, while others have focused on seed development and the specialized proteomes of distinct tissues/organs. These include the characterization of organelle proteomes such as nuclei and mitochondria, as well as proteins distributed in plasma or microsomal membranes from various tissues. The isolation of sub-cellular proteins typically requires a series of steps that are labor-intensive. Thus, efficient protocols for sub-cellular fraction, purification, and enrichment are necessary for each cellular compartment. In addition, protein extraction, solubilization, separation, and digestion prior to mass spectral identification are important to enhance the detection of low abundance proteins and to increase the overall detectable proportion of the sub-cellular proteome. This review summarizes the sub-cellular proteomics studies in Medicago truncatula.